Asbestos exposure and histological subtype of malignant mesothelioma. Issue 11 (19th August 2016) - Franklin, P; Alfonso, H; Reid, A; Olsen, N; Shilkin, K B; Brims, F; de Klerk, N; Musk, A W
Abstract : Background: Malignant mesothelioma (MM) has distinct histological subtypes (epithelioid, sarcomatoid and biphasic) with variable behaviour and prognoses. It is well recognised that survival time varies with the histological subtype of MM. It is not known, however, if asbestos exposure characteristics (type of asbestos, degree of exposure) are associated with different histological subtypes. Aim: To determine if the pathological MM subtype is associated with the type of asbestos or the attributes of asbestos exposure. Methods: Cases of MM for the period 1962 until 2012, their main histological subtype and their most significant source of asbestos exposure were collected from the Western Australian Mesothelioma Registry. Exposure characteristics included, degree of asbestos exposure (including total days exposed, years since first exposure and, for crocidolite only, calculated cumulative exposure), source of exposure (occupational or environmental), form of asbestos handled (raw or processed) and type of asbestos (crocidolite only or mixed fibres). Results: Patients with the biphasic subtype were more likely to have occupational exposure (OR 1.83, 1.12 to 2.85) and exposure to raw fibres (OR 1.58, 1.19 to 2.10). However, differences between subtypes in the proportions with these different exposure characteristics were small and unlikely to be biologically relevant. Other indicators of asbestos exposure were not associated with the histological subtype of mesothelioma. Conclusions: There was no strong evidence of a consistent role of asbestos exposure indicators in determining the histological subtype of MM.